Collagen-Based Corneal Substitutes with Incorporated Anti-infective Peptide LL37 Sustalined Deivery System - Buznyk, O. I.; Pasyechnikova, N. V.; Yakymenko, S. A.; Islam, M. M.; Griffith, M. (Ukrainian Journal of Ophthalmology, 2026)
Purpose. To develop corneal substitutes (CS) with a dual function:1) corneal stroma substitute, and 2) antiinfective peptide (AIP) delivery. Methods. AIP LL37 (cathelicidin) was encapsulated in silica nanoparticles (SINP) under the effect of magnetic field. SiNP with LL37 were then introduced in CS during their production using the method of creation of interpenetrating network of type I collagen and 2 methacryloyloxyethylphosphorylcholine. Dynamics of LL37 release from CS using ELISA method was evaluated. Refractive properties of CS with incorporated AIP release system were assessed using Abbe refractometer. Cytotoxicity of the CS to the cells of the human corneal epithelium was assessed by using WST-1 based colorimetric assay. Mechanical properties were checked by performing lamellar keratoplasty on ex vivo porcine eyes. Results. Gradual release of LL37 from within CS occurred up to 21day. Release from control CS (with incorporated free LL37) stopped on the 1st day. Refractive index (RI) of CS with LL37 in SiNP was equal to 1.3 (human cornea 1.37). There was no increased cytotoxicity of CS with incorporated release system compared to clear CS. Mechanical strength of CS with LL37 was non-significantly lower compared to clear CS. Conclusion. For the first time CS containing AIP sustained delivery system was developed. Gradual release of AIP LL37 from within CS was proved. No cell toxicity, satisfactory optical and mechanical properties of the constructs were found.